Endogenous oxidized phospholipids reprogram cellular metabolism and boost hyperinflammation - Di Gioia, Marco; Spreafico, Roberto; Springstead, James R.; Mendelson, Michael M.; Joehanes, Roby; Levy, Daniel; Zanoni, Ivan (Nature immunology, 2020)
Pathogen-associated molecular patterns (PAMPs) have the capacity to couple inflammatory gene expression to changes in macrophage metabolism, both of which influence subsequent inflammatory activities. Similar to their microbial counterparts, several self-encoded damage-associated molecular patterns (DAMPs) induce inflammatory gene expression. However, whether this symmetry in host responses between PAMPs and DAMPs extends to metabolic shifts is unclear. Here, we report that the self-encoded oxidized phospholipid oxPAPC alters the metabolism of macrophages exposed to lipopolysaccharide. While cells activated by lipopolysaccharide rely exclusively on glycolysis, macrophages exposed to oxPAPC also use mitochondrial respiration, feed the Krebs cycle with glutamine, and favor the accumulation of oxaloacetate in the cytoplasm. This metabolite potentiates interleukin-1β production, resulting in hyperinflammation. Similar metabolic adaptions occur in vivo in hypercholesterolemic mice and human subjects. Drugs that interfere with oxPAPC-driven metabolic changes reduce atherosclerotic plaque formation in mice, thereby underscoring the importance of DAMP-mediated activities in pathophysiological conditions. Oxidized host-derived phospholipids such as oxPAPC can play important roles in atherosclerosis. Zanoni and colleagues demonstrate that oxPAPC generates a distinctive metabolic and hyperinflammatory profile in macrophages that can drive atherosclerosis in mice.